Probiotic Therapy With VSL#3® in Patients With NAFLD: A Randomized Clinical Trial - Derosa, Giuseppe; Guasti, Luigina; D’Angelo, Angela; Martinotti, Chiara; Valentino, Maria Chiara; Di Matteo, Sergio; Bruno, Giacomo M.; Maresca, Andrea M.; Gaudio, Giovanni V.; Maffioli, Pamela (Frontiers in Nutrition, 2022)
Aim To evaluate if VSL#3® [a high-concentration multi-strain probiotic mix containing one strain of Streptococcus thermophilus BT01, three strains of Bifidobacteria (B. breve BB02; B. animalis subspecies [subsp.] lactis BL03, previously identified as B. longum BL03; and B. animalis subsp. lactis BI04, previously identified as B. infantis BI04), and four strains of Lactobacilli (L. acidophilus BA05, L. plantarum BP06, L. paracasei BP07, and L. helveticus BD08, previously identified as L. delbrueckii subsp. bulgaricus BD08)] therapy could improve hepatic parameters. Methods We enrolled 60 Caucasian patients aged ≥ 18 years of either sex with the diagnosis of non-alcoholic fatty liver disease (NAFLD), according to practice guidance, in a double-blind, placebo-controlled study. Patients were randomized to take placebo or VSL#3®, 2 sachets/day in the morning for 3 months. VSL#3® and placebo were self-administered. Results We did not observe any change in body mass index (BMI), circumferences, fasting plasma glucose (FPG), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-C), high-density lipoprotein-cholesterol (HDL-C), and adiponectin (ADN) with neither treatment. A statistically significant triglycerides (Tg) decrease (p < 0.05 vs. baseline, and p < 0.05 vs. placebo, respectively) and high-sensitivity C-reactive protein (Hs-CRP) decrease (p < 0.05 vs. baseline) was observed in the group of patients being treated with VSL#3® compared with placebo. Transaminases and gamma-glutamyltransferase (γ-GT) were significantly reduced in VSL#3® group (p < 0.05 vs. baseline and placebo, respectively) compared with the placebo group. Aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio and hepatic steatosis index (HSI) were significantly lower than the VSL#3® group (p < 0.05 vs. baseline and placebo, respectively) compared with the placebo group. All patients reported an improvement or the disappearance of hepatic steatosis. Conclusion Probiotic therapy with VSL#3® ameliorates hepatic parameters and echography grading, while reducing Tg and the inflammatory status, without any difference between men and women.